Effects of Protein A in Detection of Canine Distemper Virus through immunosensor construction - Basso, Caroline Rodrigues [UNESP]; Sempionatto, Juliane R. [UNESP]; Tozato, Claudia C. [UNESP]; Castro, Gustavo Rocha de [UNESP]; Araujo Júnior, João Pessoa [UNESP]; Pedrosa, Valber A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2015)
We have developed a detection system to canine distemper virus (CDV) by employing surface plasmon resonance (SPR) and compared the effect of oriented and random immobilization. Several parameters, such as the surface concentration of immobilized antibodies, antigen binding capacity, and the maximum surface concentration of immobilized antibody were optimized. The maximal antigen binding capacity was obtained by means of a SPR-sensor immobilized via protein A, which leads to an end-on orientation. CDV at 0.1 ng/mL can be detected using protein A. Urine analysis showed that all samples contained detectable levels of CDV, but the results revealed an improvement in sensitivity of the assay when it is specifically oriented. The described method is simple, fast, selective, and sensitive to the biorecognition element. The results emphasize how important it is to attach proteins on surfaces in such a way that their binding sites are oriented toward the solution phase.
Keywords: Antibody; Canine distemper virus; Immunosensor; Oriented immobilization; Protein A